K-Workers Competencies Among Alumni University - Teguh Iman Santoso; Muhammad Nurwaskita Alamsyah; Dwi Urip Wardoyo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This study investigates the impact of various competencies on the development of K-Worker competencies among alumni from the Faculty of Economics at University X. The primary focus areas include Technical Competence, Human and Social Competence, and Learning Competence and Methodology. The analysis reveals a significant difference in Technical Competence between the cohorts of 2021 and 2022, with a notable p-value of 0.010. This finding underscores the critical role of technical skills in professional development. However, no significant differences were observed in Human and Social Competence and Learning Competence and Methodology, with p-values of 0.569 and 0.780, respectively. These results suggest a consistent approach in developing these skills across cohorts. The study contributes to the enhancement of curriculum design and alignment of educational outcomes with workforce requirements, ensuring graduates are well-prepared for the demands of the digital economy. Future research should focus on longitudinal assessments of alumni competencies and the impact of specific learning methodologies on competency development to provide a comprehensive understanding of how educational programs influence K-Worker competencies. This study is novel in its specific focus on economics graduates and its comprehensive assessment of multiple competencies across different cohorts